Korelasi Antara Kandungan Karbohidrat, Protein, dan Lemak dengan Kompatibilitas Grafting Bibit Durian (Durio zibethinus Murr.) - Suharjo, Suharjo (Universitas Bangka Belitung, 2019)
Durian nurseries can be done using generative and vegetative material sources. Both sources of propagation have their respective weaknesses and strengths. Quality seeds are obtained through a combination of two sources of propagation material that have each of the advantages that can complement each other. The process of merging can be through mini grafting. The mini grafting method in durian nurseries can use side grafting and shoot grafting methods. This study wants to examine the relationship of carbohydrate, protein, and fat content to the successful growth of mini grafting results on durian plants. The research was carried out by analyzing the carbohydrate, protein and fat content in the upper stem which will be used for grafting, as well as observing and measuring the growth process of mini grafting plants. It was concluded that the carbohydrate content of the upper stems gave the highest positive contribution to the increase in the number of shoots followed by the number of leaves, percentage of living grafts, leaf area, leaf area ratio, root canopy ratio, shoot length, and stem diameter. The protein and fat content cannot contribute to the growth even has a tendency to inhibit growth of grafted seeds.